Between romantic and confluent love: social representations of love among young lesbians from Lima’s upper class - Giesecke, Micaela (2019)
Love has been subject of interest to various areas of knowledge, art and everyday life. From the field of sociology, this paper aims to analyze social representations of love among young lesbians of Lima’s upper class. The focus is on how their trajectories, families and self-identification influence the construction of such representations. Nine interviews were conducted with young lesbians from the upper class to answer the research question. Two approaches to love were found: from romantic to confluent love and towards confluent love. Moreover, it was found that this love holds three secrets: the secret of the inner world, the secret that is kept from their families and the environment and the one that is hidden from their partners. The aforementioned is linked, among other factors, to the specificity of being lesbians from Lima’s upper class.